2017
DOI: 10.3233/cbm-170205
|View full text |Cite
|
Sign up to set email alerts
|

A 4-miRNAs signature predicts survival in glioblastoma multiforme patients

Abstract: The 4-miRNA signature was identified as an independent prognostic biomarker that identified patients who have a favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…In that regard, previous studies detected GBM-associated EVs in patient plasma (Jones et al, 2019), elevated levels of miR-9 in GBM tissues (Wu et al, 2013) and in the serum-derived EVs (Ji et al 2016) and cerebrospinal fluid (CSF) (Sørensen et al 2017) of acute ischemic stroke patients, suggesting miR-9 as a potential liquid biopsy marker for GBM progression and brain damage. The prognostic value of miR-9 levels has already been endorsed with its inclusion in multi-marker prognostic panels for GBM (Yuan et al, 2017). Our study supports these results by providing a mechanistic role of miR-9 in GBM progression.…”
Section: Discussionsupporting
confidence: 86%
“…In that regard, previous studies detected GBM-associated EVs in patient plasma (Jones et al, 2019), elevated levels of miR-9 in GBM tissues (Wu et al, 2013) and in the serum-derived EVs (Ji et al 2016) and cerebrospinal fluid (CSF) (Sørensen et al 2017) of acute ischemic stroke patients, suggesting miR-9 as a potential liquid biopsy marker for GBM progression and brain damage. The prognostic value of miR-9 levels has already been endorsed with its inclusion in multi-marker prognostic panels for GBM (Yuan et al, 2017). Our study supports these results by providing a mechanistic role of miR-9 in GBM progression.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, Yuan et al [57] found increased levels of let-7g-5p, miR-139-5p, miR-17-5p, and miR-9-3p in tumor tissue samples from long-term glioblastoma survivors independent of their MGMT methylation status. Patients with high expression levels of these miRNAs lived 88 days longer than patients with low expression levels (439 vs. 351 days, respectively) [57].…”
Section: Long-term Glioblastoma Survivorsmentioning
confidence: 97%
“…This can be partially explained with better overall health, but it can also be a result of different molecular and genetic alterations in younger compared to older patients [5]. Although glioblastomas from short-and long-term survivors are histologically the same, their biological and molecular characteristics are remarkably different [57].…”
Section: Long-term Glioblastoma Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating studies have identified multiple dysregulated miRNAs, which may serve as key molecules in cancer progression, and regulate various biological processes, including proliferation, differentiation, apoptosis and survival (8)(9)(10). Previous studies have demonstrated a significant difference in the expression profile of miRNAs between healthy subjects and patients with glioma, suggesting that the expression levels of certain miRNAs are associated with the overall survival (OS) of glioma patients (11)(12)(13)(14). Therefore, the identification of differentially expressed miRNAs is of great importance in order to evaluate the early prognosis of glioma patients.…”
Section: Introductionmentioning
confidence: 99%